Developing English Vocabulary Learning Game - Widya Adhariyanty Rahayu; Suastika Yulia Riska (LPMPP Universitas Negeri Yogyakarta, 2018)
Abstract: The purpose of this study was to develop an English vocabulary game as learning media for students majoring in informatics and management. Research and Development (RD) approach was employed in this study. This study involved several steps, namely needs analysis, material development, expert validation, try out, and final product. The result of the needs analysis showed that the students found it difficult to understand English vocabularies so they needed fun learning media to motivate themselves. The material development stage resulted in vocabulary learning media that is “English with Ido”. The expert validation involved media and material experts. The percentage of media eligibility obtained from the media expert was 76, 78% or it was very decent; while the percentage of the material feasibility obtained from the material expert was 75% or it was decent to use as learning media. The try out cycle involved students majoring in informatics and management program. Based on judgment from the media and material expert as well as from the respondents of this study, it can be concluded that the final product of the English vocabulary game was considered as good learning media. PENGEMBANGAN MEDIA PEMBELAJARAN GAME KOSAKATA BAHASA INGGRIS Abstrak: Penelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis game kosakata Bahasa Inggris pada program studi teknik informatika dan manajemen. Metode yang digunakan adalah Research and Development (RD). Tahap penelitian meliputi need analysis, material development, expert validation, try out, dan final product. Hasil tahap need analysis adalah mahasiswa masih sulit memahami kosakata Bahasa Inggris, maka diperlukan media pembelajaran yang menyenangkan sehingga bisa memotivasi mahasiswa dalam proses belajar mengajar. Pada tahap material development menghasilkan media pembelajaran berbasis game kosakata English with Ido. Tahap expert validation dilakukan dengan melibatkan ahli media dan ahli materi untuk menilai kelayakan produk. Pada tahap ini presentase kelayakan berdasarkan ahli media adalah 76,78% (sangat layak) dan presentase ahli materi adalah 75% (layak) untuk digunakan sebagai media pembelajaran. Tahap try out dilakukan pada responden mahasiswa program studi teknik informatika dan manajemen. Dari tahap-tahap tersebut dan saran dari ahli media, ahli materi, serta responden maka dihasilkan produk final berupa game media pembelajaran kosakata Bahasa Inggris. Kata Kunci: media pembelajaran, game, kosakata bahasa Inggris